PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMA NEGERI 1 KAMPAR - Husni, Muhammad Ali; ', Rasmiwetti; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research was aimed to improve study result of student on solubility and result times solubility subject has been doing in class XI science SMAN 1 Kampar. This research was a form of experiments research with design pretest-posttest. Sample of the research were student of class XI science 2 as experimental class and class XI science 3 as control class. The experimental class was applied learning model problem base learning while the control class using discussion method. Data were analized using t- test. Result from the data analysis showed t count > t table (1,6923 > 1,68). It means learning model problem based learning can increase study result of student on solubility and result times solubility subject in class XI science SMAN 1 Kampar with category of increase study results on the solubility and result times solubility in class XI science is high category.Key Word: study results, problem based learning, solubility and result time solubility